2013
DOI: 10.1111/1468-2230.12030
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Labels, the European Convention on Human Rights and the Presumption of Innocence

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 54 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…A second line of argument claims that practices of disclosure and publicity fail to serve the purposes to which they are usually put – namely just punishment (Hadjimatheou, 2016; Lippke, 2018) and public protection (Henley, 2019) – and are therefore difficult to justify on those grounds. Finally, a third layer of critique questions the compatibility of criminal record disclosure with respect for human rights, specifically rights to privacy (Grace, 2014; Larrauri, 2014b), rehabilitation (Hoskins, 2019) and the presumption of innocence (Campbell, 2013; Larrauri, 2014a; Purshouse, 2018). To what extent can these insights help us to understand the normative implications of DADS?…”
Section: Moral and Legal Issues With Disclosure Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…A second line of argument claims that practices of disclosure and publicity fail to serve the purposes to which they are usually put – namely just punishment (Hadjimatheou, 2016; Lippke, 2018) and public protection (Henley, 2019) – and are therefore difficult to justify on those grounds. Finally, a third layer of critique questions the compatibility of criminal record disclosure with respect for human rights, specifically rights to privacy (Grace, 2014; Larrauri, 2014b), rehabilitation (Hoskins, 2019) and the presumption of innocence (Campbell, 2013; Larrauri, 2014a; Purshouse, 2018). To what extent can these insights help us to understand the normative implications of DADS?…”
Section: Moral and Legal Issues With Disclosure Schemesmentioning
confidence: 99%
“…On this account, disclosures of non-conviction data under DADS would certainly violate the presumption of innocence and be objectionable on that ground, because in the words of Grace (2021: 144) they ‘carry the weight of official confirmation of risk’. Against this, Campbell has argued convincingly that the stigmatisation included in an official declaration of riskiness or suspicion is qualitatively different from that of an official declaration of criminal guilt (Campbell, 2013). The fact that DADS only involve a declaration of risk and that disclosure is made to a single individual alone means that both the severity and scope of stigmatisation are significantly reduced compared with an official declaration of guilt.…”
Section: Moral and Legal Issues With Disclosure Schemesmentioning
confidence: 99%
“…as this approach is well established, this article argues that it is instead the addition of AI to predictive policing that has made its use much more efficient and arguably less compatible with existing legal procedures. 9 With AI it is possible to correlate a multitude of otherwise unrelated factors that are not easily comparable or reconcilable. Such an algorithm is notable in its ability to perform quick calculations in real-time, but also to quantify and compare seemingly unrelated data points.…”
Section: Preventing Crime With Ai: Predictive Policingmentioning
confidence: 99%
“…Were the Court to address such an expanded use of acquitted individuals' data to form pre-emptive suspicion, it may reach an even more expanded reading of the presumption. 67 The Court's strong approach to applying the presumption to postacquittal treatment is notable for the case of predictive policing. Predictive analyses rely heavily on crime data that include and prioritize arrest records and non-custodial stops.…”
Section: Presumption Of Innocencementioning
confidence: 99%
“…26To an already problematic situation we could include here additional considerations of personal reputation and ‘good name’. See Campbell (2013b, pp. 705–706), where it is suggested that: ‘while the ostensible rationale [of civil recovery] is to recoup unlawfully acquired assets, and while these orders are directed at the property rather than the person, recovery also incorporates a substantial stigma and incorporates the blame that distinguishes criminal from civil measures, with the former connoting “should not do”’ (references omitted).…”
mentioning
confidence: 99%